Model Manajemen Mutu Bagi BAZNAS Dan LAZ Di Indonesia (UIN Sunan Kudus, 2018)
This study aims to find out the quality management models used by National Zakat Board (BAZNAS) and the Institute for Amil Zakat (LAZ) in Indonesia. This study uses qualitative descriptive method with literature review as the main study material. The results of the study show that there are several models and forms of quality management selected by zakat management organizations in Indonesia. Most choose ISO as a reference in testing the performance quality of their institutions. This choice is taken because it tends to be more familiar among the people and has been used in companies in Indonesia even in the world. Zakat Forum introduces other quality management models besides ISO, namely Zakah Criteria for Performance Exellence. This model is considered more suitable with the characteristics of zakat, because it can identify the strengths and weakness as a whole with reference to the seven criteria. The basic value and framework of this quality management model is based on the Qur'an and hadith so that it is more Islamic.